Letter (copy) : Position at Santander - Tewson, Vincent
011-0064-001 HVT/FC/EW/133 Secretary's 13th July, 1937. Senor J.I. de Lizaso, Spanish Embassy, 24, Belgrave Square, S.W.1 Dear Senor Lizaso, Position at Santander Your letter of the 6th July addressed to Sir Walter arrived whilst he was out of the country, and I am not expecting him back this week. I have made certain enquiries in regard to the difficulties which you raise, I now believe that position is greatly improved. I understand that ships conveying food and refugees now entering and leaving Santander. I sincerely hope that the position is a little easier. Sir Walter will be back on Monday should any emergencies arise upon which you require his assistance. Yours sincerely, Assistant Secretary 292/946/11/64